AMP-activated protein kinase α1-sensitive activation of AP-1 in cardiomyocytes. (August 2016) - Voelkl, Jakob; Alesutan, Ioana; Primessnig, Uwe; Feger, Martina; Mia, Sobuj; Jungmann, Andreas; Castor, Tatsiana; Viereck, Robert; Stöckigt, Florian; Borst, Oliver; Gawaz, Meinrad; Schrickel, Jan Wilko; et al.
Abstract: AMP-activated protein kinase (Ampk) regulates myocardial energy metabolism and plays a crucial role in the response to cell stress. In the failing heart, an isoform shift of the predominant Ampkα2 to the Ampkα1 was observed. The present study explored possible isoform specific effects of Ampkα1 in cardiomyocytes. To this end, experiments were performed in HL-1 cardiomyocytes, as well as in Ampkα1-deficient and corresponding wild-type mice and mice following AAV9-mediated cardiac overexpression of constitutively active Ampkα1. As a result, in HL-1 cardiomyocytes, overexpression of constitutively active Ampkα1 increased the phosphorylation of Pkcζ. Constitutively active Ampkα1 further increased AP-1-dependent transcriptional activity and mRNA expression of the AP-1 target genes c-Fos, Il6 and Ncx1, effects blunted by Pkcζ silencing. In HL-1 cardiomyocytes, angiotensin-II activated AP-1, an effect blunted by silencing of Ampkα1 and Pkcζ, but not of Ampkα2. In wild-type mice, angiotensin-II infusion increased cardiac Ampkα1 and cardiac Pkcζ protein levels, as well as c-Fos, Il6 and Ncx1 mRNA expression, effects blunted in Ampkα1-deficient mice. Pressure overload by transverse aortic constriction (TAC) similarly increased cardiac Ampkα1 and Pkcζ abundance as well as c-Fos, Il6 and Ncx1 mRNA expression, effects again blunted in Ampkα1-deficient mice. AAV9-mediated cardiac overexpression of constitutively active Ampkα1 increased Pkcζ protein abundance and the mRNA expression of c-Fos, Il6 and Ncx1 in cardiac tissue. In conclusion, Ampkα1 promotes myocardial AP-1 activation in a Pkcζ-dependent manner and thus contributes to cardiac stress signaling. Highlights: Cardiac Ampkα1 is upregulated by pressure overload and angiotensin-II infusion. Ampkα1 activates the transcription factor AP-1 via Pkcζ in cardiomyocytes. AP-1 activation by angiotensin-II is blunted by silencing of Ampkα1 but not Ampkα2. Cardiac Ampkα isoform shift may contribute to the signaling of cardiac remodeling.